2013
DOI: 10.4025/actascianimsci.v35i1.15155
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate without shade and silvopastoral system during summer and winter

Abstract: This study evaluated the microclimate in a system without shade (WS) and in a silvopastoral system (SP) with eucalyptus during summer and winter, by measuring the air temperature (Ta), black globe temperature (Tg), relative humidity (RH), wind speed (Ws), every 2 hours for 24 hours between rows, shade (SP) and no shade effect (WS). It was employed the randomized blocks design (months), in the plots (systems), subplots (hours) and sub-subplots (seasons). Except for Ta and RH, the Tg ( 24.73, 26.41ºC), Ws (3.16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
(23 reference statements)
1
19
0
1
Order By: Relevance
“…Similar results were obtained in other silvopastoral systems using rows (Baliscei et al, 2013) or for other crops under systems arranged with tree rows (Pezzopane et al, 2010). The relative humidity values (directly related to temperature) showed that, with lower air removal at the midpoint between rows, there were higher values (maximum and average) found at this sample point.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Similar results were obtained in other silvopastoral systems using rows (Baliscei et al, 2013) or for other crops under systems arranged with tree rows (Pezzopane et al, 2010). The relative humidity values (directly related to temperature) showed that, with lower air removal at the midpoint between rows, there were higher values (maximum and average) found at this sample point.…”
Section: Resultssupporting
confidence: 74%
“…This observation demonstrates the importance of plant arrangement in tree rows acting as windbreaks. Baliscei et al (2013), Souza et al (2010) found that, in terms of reduced incidence of winds, microclimatic changes in the silvopastoral systems promoted better animal comfort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The silvopastoral system has been considered a good option for cattle-rearers to recover degraded pasture (Dubè et al 2002) as the trees in the pasture may improve the forage nutritional quality (Jackson and Ash 1998;Carvalho et al 2002;Tripathi et al 2005;Souza et al 2010) and animal comfort (Baliscei et al 2013). Tree cover can increase forage biomass (Souza et al 2010) or decrease it, if shading is too high (Jackson and Ash 1998;Rozados-Lorenzo et al 2007;Paciullo et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…() have suggested that an option for sustainable livestock production is the adoption of silvopastoral system (SPS). Among the productive and environmental benefits of the SPS, the following stand out: Improved soil nutrient availability, increased animal production associated with thermal comfort, and higher crude protein (CP) content of forage, as well as the possibility of income diversification in the property (Baliscei et al., ; Kyriazopoulos, Abraham, Parissi, Koukoura, & Nastis, ; Murgueitio, Calle, Uribe, Calle, & Solorio, ; Paciullo et al., ), and environmental services, such as increased biodiversity, sequestration of atmospheric carbon and mitigation of greenhouse gases (Alves, Madari, & Boddey, ; López‐Carrasco, López‐Sánchez, San Miguel, & Roig, ).…”
Section: Introductionmentioning
confidence: 99%